PROSPEK PENYELENGGARAAN SISTEM RESI GUDANG (SRG) SEBAGAI INSTRUMEN SUMBER PEMBIAYAAN DAN PENINGKATAN PENDAPATAN PETANI JAGUNG - Anugrah, Iwan Setiajie; Saputra, Yonas Hangga; Erwidodo (Analisis Kebijakan Pertanian, 2024)
This study aims to identify and analyze the performance of the Warehouse Receipt System (SRG) for maize, with the main focus on increasing incomes and making SRG a source of financing for maize farmers. The study was conducted purposively in maize center provinces/districts in FY 2015, involving the provinces of East Java, West Nusa Tenggara, and West Java. Respondents included SRG managers, maize farmers, users, actors, and the role of SRG-related institutions at the center and research locations. The analysis method follows the mechanism of Bappebti’s SRG scheme, with data presented and analyzed descriptively. Results show that the implementation of maize SRG is still limited and slow nationwide, with the number of SRGs reaching only 165 by 2021. Constraints include storage volume limits, storage quality, farmers’ need for quick funds, yield linkages with financiers, farmers’ limited understanding and trust in SRG, and competing government/non-government programs related to financing sources. However, there is potential for improvement through greater participation from farmers, maize groups/groups, and corporations, with expanded understanding through socialization, advocacy, and the active role of local governments to ensure the sustainability and positive impact of maize SRG in the three research locations.